Sistem Informasi Pengelolaan Data Nilai Rapor Berbasis Web Pada SDN 008 Tanjungpinang Timur - Liza Safitri; Hafidah Muna Rhima Dani (Jurnal Bangkit Indonesia, 2019)
SDN 008 TANJUNGPINANG TIMUR is an educational institution established in 1973 in Tanjungpinang city with the guarantee of boosting students’ learning motivation in a fun and engaging manner. Education is therefore considered as a process that leads to the change of knowledge, attitude and mentality of students. A report card is a method to measure students’ performances. A system analysis aims to understand how the intricacies of the system under research and development work. The result of the system analysis is a report that describes the system under study and its problems as well as to create a newly developed system design. The designed data management information system of the report cards has the characteristics of being able to support the process of monitoring students’ performances quickly and efficiently. Therefore the proposed system design is further developed into a website-based system so that it facilitates the process of delivering all information to all teachers as a form of transparency to both the school party and students’ parents.